5 Plaque erosion pilot study. (27th November 2017) - Chandran, Sujay; Watkins, Johnathan; Abdul-Aziz, Amina; Calvert, Patrick A; Bowles, Kristian M; Flather, Marcus D; Rushworth, Stuart A; Ryding, Alisdair D
Abstract : Background: Plaque erosion causes 30% of STEMI cases, but the underlying cause is unknown. Inflammatory infiltrates are less abundant in erosion compared to rupture in autopsy studies. Objectives: We hypothesised that erosion and rupture are associated with significant differences in intracoronary cytokines in vivo . Methods: 40 STEMI patients with <6 hours of chest pain were classified as ruptured fibrous cap (RFC) or intact fibrous cap (IFC) using optical coherence tomography. Plasma samples from the infarct-related artery and a peripheral artery were analysed for expression of 102 cytokines using arrays: results were confirmed with ELISA. Thrombectomy samples were analysed for differential mRNA expression using RT-PCR. Results: 23 lesions were classified as RFC (58%), 15 as IFC (38%) and 2 were undefined (4%). 12% (12/102) of cytokines were differentially expressed in both coronary and peripheral plasma. CXCL11 was preferentially expressed in RFC (SAM adjusted p<0.001; ELISA IFC 10.2 vs RFC 10.8 log2 pg/ml; p=0.042). IFC was associated with preferential expression of Epidermal Growth Factor (SAM adjusted p<0.001; ELISA IFC 7.42 vs RFC 6.63 log2 pg/ml, p=0.036) and thrombospondin-1 (TSP-1) (SAM adjusted p=0.03; ELISA IFC 10.4 vs RFC 8.65 log2 ng/ml, p=0.0041). Thrombectomy mRNA showed elevated CXCL11 in RFC (p=0.0007) EGF expression in IFC (p=0.0264) and, but no differences in expression of TSP-1. Conclusions: These results demonstrate differential intracoronary cytokine expression in RFC and IFC. Elevated TSP-1 and EGF may play an aetiological role in erosion.